The impact of a new method for the detection of Mycobacterium avium subspecies paratuberculosis on the control of Johne's disease in dairy cattle - Gerrard, Zara Elizabeth (2018)
Johne’s disease (JD) is a severe wasting disease of ruminants, characterised by chronic enteritis, reduction in milk yield, and severe weight loss despite a maintained appetite. The causative agent is Mycobacterium avium subspecies paratuberculosis (MAP), a slow growing pathogen that can take up to 18 weeks for detection on solid culture. Control programmes rely on sensitive diagnostics to identify infected animals quickly so they can be either removed from the herd or managed differently to control the spread of disease. Unfortunately, the Gold Standard of detection is culture, which due to decontamination procedures, has low sensitivity. Enzyme-linked immunosorbent assays (ELISA) are used more often than faecal culture within control programmes as they are cheaper and quicker than culture methods. However, they only detect the animal’s immune response, rather than the causative agent. This can cause some issues with diagnosis as the immune response can be affected by other variables. Therefore, to effectively control disease, a new detection method needs to be developed. In this series of studies, phage-PCR was used within large scale on-farm sampling to establish its performance against the Gold Standard (liquid culture with ESP-trek) and MAP specific antibody milk ELISA (ab-ELISA). Phage-PCR is thought to be more sensitive than other methods due to its low limit of detection. It is also rapid and relatively inexpensive. Results suggest that phage-PCR can detect more animals shedding MAP into their milk than other methods, or in the least a different group of animals than the other methods. There was some evidence that animals who have had an ab-ELISA positive result in the last year are shedding less MAP into their milk, suggesting that the immune response is helping to control the disease in the short-term. However, this was not observed beyond one year. Phage-PCR had a better agreement with faecal culture than milk culture or ab-ELISA, but this was limited. There was also evidence that early detection could be achieved, as some animals were identified as faecal shedding with phage-PCR before they had seroconversion and detected with a-ELISA. However, it must be noted that these animals may not be infected and just passaging MAP through the GI tract from the contaminated environment. An investigation into the prevalence of MAP in pasteurised milk using phage-PCR was also carried out. There is thought to be an association between MAP and Crohn’s Disease, with milk highlighted by some as a key transmission vector. There was an increase in the proportion of samples containing viable MAP when compared to other surveys within the literature. However, this was thought to be due to the lower limit of detection that phage-PCR provides, rather than an increase in prevalence. Phage-PCR can be used effectively for large-scale on-farm sampling to identify animals shedding MAP into the milk. However, some changes to the assay and sample processing will have to be undertaken before this can be used within industry as its current format is laborious and not suited to automation. Until then, it could be used as a tool to further research and understanding into JD in dairy cattle.